CLONING OF ProAV PROMOTER ISOLATED FROM TIGER PRAWN Penaeus monodon - Andi Parenrengi; Alimuddin Alimuddin; Sukenda Sukenda; Komar Sumantadinata; Muhammad Yamin; Andi Tenriulo (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2009)
Promoter is a specific DNA sequence involved in the transcription of a particular gene. It is usually located in the upstream of the gene they regulate. Isolation and characterization of promoter is essentially needed in order to establish the sequence analysis and transcription factor that are used in the regulation of gene expression. The research was conducted to analyze the characteristics of Penaeus monodon anti viral gene promoter (ProAV) towards generation of auto-transgenic tiger prawn, P. monodon. ProAV promoter was isolated by PCR (Polymerase Chain Reaction) method and the purified DNA fragment was cloned into pGEM-T Easy cloning vector. The promoter sequence was characterized by using BLAST-N and Genetyx version 7 softwares. The results showed the success in isolating a promoter from tiger prawn of 368 bp in length. BLAST-N analysis showed that the sequence of isolated promoter has high similarity (95%-98%) compared to the other promoters in the GeneBank. The study revealed the existence of important transcription factors (TATA box, MRE, TCF-1, and other potential regulatory elements) are identified in the promoter sequence.